2011
DOI: 10.1177/1538574411422117
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Intolerance During Flow Arrested Carotid Angioplasty

Abstract: Carotid angioplasty with stenting can be safely conducted with flow arrest as an alternative to filter-type cerebral protection devices. However, because cerebral intolerance is not an infrequent occurrence with this approach, clinicians must be cognizant of management strategies for transient cerebral intolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Advanced age is a recognized risk factor for poor outcomes in CEA, and some studies have shown increasing patient age to be a risk factor for stroke in CAS At our institution, we continued to adopt CAS in the infrequent occurrence with this approach, clinicians must be aware of management strategies for transient cerebral intolerance 11) .…”
Section: Discussionmentioning
confidence: 99%
“…Advanced age is a recognized risk factor for poor outcomes in CEA, and some studies have shown increasing patient age to be a risk factor for stroke in CAS At our institution, we continued to adopt CAS in the infrequent occurrence with this approach, clinicians must be aware of management strategies for transient cerebral intolerance 11) .…”
Section: Discussionmentioning
confidence: 99%